Juridical Analysis Of The Practice Of Renting Back Shophouses To Other Parties Without Permission From The Shophouse Owner (Case Study Of Decision Number 6/Pdt.G.S/2024/Pn Sit) - Sulistyo, Luthfiani Bintang; Sulastri, Sulastri (PALAR (Pakuan Law review), 2025)
The purpose of this research is to examine civil law perspectives on the practice of subleasing a shop house (ruko) to a third party without the owner’s consenct, as well as to analyze the legal remedies available to the shop house owner in order to recover losses suffered as a result of Decision Number 6/Pdt.G.S/2024/PN Sit. This study employs a normative juridical method using a statute approach and a case approach. The results indicate that, form a civil law standpoint, the practice of subleasing without the owner’s permission is an act that contradicts the principle of good faith and violates the provions of lease aggrements, particularly as stipulated in Article 1559 of the Indonesian Civil Code, and therefore can be classified as a breach of contract. To recover the losses resulting from the lessee’s actions and the aforementioned court decision, the shop house owner has the right to pursue various legal remedies, including ordinary legal remedies such as appeal and cassation, as well as extraordinary legal remedies such as judicial review (Peninjauan Kembali or PK).Keyword: Lease Agreement, Subleasing, Default